Perlindungan Hukum Terhadap Korban Penyalahgunaan Narkotika - Bumi, Salyo Kinasih; Supolo, Supolo; Nugroho, Bastianto (Fakultas Syariah INSURI Ponorogo, 2022)
Currently, the circulation of narcotics in Indonesia has penetrated almost all elements of society, starting from the elite, politicians, public figures, students and university students. This condition is certainly very concerning because the use of narcotics can affect the patient's feelings, thoughts and awareness. Narcotics which were originally only used for medical purposes as anesthetics and painkillers or painkillers, are now widely misused. Narcotics and psychotherapy crimes are serious crimes against humanity. Rehabilitation is a repressive measure carried out for drug addicts. Rehabilitation measures are aimed at victims of narcotics abuse to restore the physical, mental, and social abilities of the sufferer concerned, with the hope that the addict can recover from his addiction to narcotics. Indonesia is a state of law, showing evidence of seriousness in tackling narcotics abuse with the issuance of Law No. 35 of 2009 concerning Narcotics which regulates efforts to eradicate narcotics crimes through threats of fines, imprisonment, life imprisonment, and death sentences and regulates the use of narcotics. for the benefit of treatment and health and regulates medical and social rehabilitation. This research uses a normative method, based on a literature study. Information is obtained from various literatures and compiled based on the results of the study from the information obtained. The primary legal materials used are; Law Number 35 of 2009 concerning Narcotics, Joint Regulation of the Chairman of the Supreme Court of the Republic of Indonesia Minister of Law and Human Rights of the Republic of Indonesia Minister of Health of the Republic of Indonesia Minister of Social Affairs of the Republic of Indonesia Attorney General of the Republic of Indonesia Head of the National Police of the Republic of Indonesia Head of the National Narcotics Agency of the Republic of Indonesia Number 01 /Pb/Ma/III/2014 Number 03 of 2014 Number 11 of 2014 Number 03 of 2014 Number Per-005/A/Ja/03/2014 Number 1 of 2014 Number Perber/01/III/2014/Bnn concerning Handling of Narcotics Addicts and Victims of Narcotics Abuse Into Rehabilitation Institutions. Meanwhile, secondary legal materials cover all principles, provisions, and legal technical procedures, both in laws and regulations, agreements and legal searches (doctrine) and literature. The collected legal materials are selected and sorted according to the topic of study to be analyzed using descriptive and argumentative techniques.